استخدام النسب المالية في التنبؤ بالفشل المالي للمؤسسات الاقتصادية - مجدوب, علاء الدين (Universty of Eloued جامعة الشهيد حمه لخضر, 2022)
الملخص: هدفت هذه الدراسة إلى استخدام النسب المالية للتنبؤ بالفشل المالي للمؤسسات الاقتصادية، وذلك من خلال محاولة بناء نموذج رياضي مكون من نسب مالية، لعينة من شركات المساهمة المدرجة في بورصة الكويت، والبالغ عددها (30) شركة نصفها شركات ناجحة ونصفها الآخر شركات فاشلة، خلال الفترة الممتدة من 2017 إلى 2019، فالتنبؤ بالفشل المالي لشركات المساهمة في وقت مبكر يعطي مؤشرا للجهات المعنية للتدخل واتخاذ الإجراءات التصحيحية المناسبة قبل أن تفشل الشركة نهائيا، وقد تم حساب ثلاثون (30) نسبة من القوائم المالية لهذة الشركات وتحليلها وفق أسلوب الاحصائي المعروف بالتحليل التمييزي، ومن ثم اختبار القدرة التنبؤية للنموذج ومقارنتها بالقدرة التنبؤية لنموذج ألتمان الثاني، نموذج كيدا ونموذج شيروود على نفس العينة. وقد توصلت الدراسة إلى بناء نموذج يتكون من خمسة نسب مالية، لها القدرة على التمييز بين الشركات الناجحة والفاشلة، حيث بلغت دقة التصنيف الكلية للنموذج المشتق 83.3%، بينما بلغت الدقة التصنيفية لنموذج ألتمان الثاني، نموذج كيدا ونموذج شيروود 55.56%، 47.78% و75.56% على التوالي، وهو مايدل على أن النموذج المقترح هو الأفضل والأقدر بين المؤسسات الناجحة والفاشلة مقارنة بنموذج ألتمان الثاني، نموذج كيدا ونموذج شيروود المعروفة عالميا. وخلصت الدراسة إلى مجموعة من التوصيات أهمها امكانية استخدام النموذج المقترح من قبل البورصة والحكومة والتجار والمستثمرين الحاليين والمرتقبين في التنبؤ بالفشل المالي لشركات المساهمة المدرجة في بورصة الكويت، كما أوصت الدراسة بإدراج المؤشرات غير المالية مثل حجم الشركة وعمر الشركة، والمتغيرات الإقتصادية إلى جانب المؤشرات المالية والمتمثلة بالنسب المالية عند بناء نماذج رياضية للتنبؤ بالفشل المالي. Résumé :فرنسية أو انجلزية This study aimed to use financial ratios to predict the financial failure of economic institutions, by trying to build a mathematical model consisting of financial ratios, for a sample of joint stock companies listed on the Kuwait Stock Exchange, numbering (30) companies, half of which are successful companies and the other half are failed companies, during the period Extending from 2017 to 2019, as predicting the financial failure of joint stock companies at an early stage gives an indication for the concerned authorities to intervene and take appropriate corrective measures before the company finally fails. Thirty (30) percentages of the financial statements of these companies have been calculated and analyzed according to the statistical method known as analysis. Then the predictive ability of the model was tested and compared with the predictive ability of the second Altman model, Kida model and Sherrod model on the same sample. The study reached to build a model consisting of five financial ratios that have the ability to distinguish between failure and non-failure companies, where the overall classification accuracy of the derived model reached 83.3%, while the classification accuracy of the second Altman model, Kida model and Sherrod model reached 55.56%, 47.78% and 75. 56%, respectively, which indicates that the proposed model is the best and most efficient among the successful and failed institutions compared to the second Altman model, Kida model and Sherrod model that globally known. The study concluded with a set of recommendations, the most important of which is the possibility of using the proposed model by the Stock Exchange, the government, traders and current and prospective investors in predicting the financial failure of joint stock companies listed on the Kuwait Stock Exchange, the study also recommended the inclusion of non-financial indicators such as company size, company age, and economic variables in addition to financial indicators represented by financial ratios in building mathematical models to predict financial failure.
دراسة حالة عينة من شركات المساهمة المدرجة في بورصة الكويت خلال الفترة (2017-2019)
أطروحة دكتوراه تخصص الإدارة المالية في العلوم الإقتصادية
Keywords: التنبؤ، الفشل المالي، النسب المالية، مؤسسات ناجحة، مؤسسات فاشلة، التحليل التمييزي، نموذج ألتمان الثاني، نموذج كيدا، نموذج شيروود، بورصة الكويت.; prediction, financial failure, financial ratios, non-failed institutions, failed institutions, discriminant analysis, Altman II model, Kida model, Sherrod model, Kuwait Stock Exchange.